2001
DOI: 10.4049/jimmunol.167.9.4821
|View full text |Cite
|
Sign up to set email alerts
|

Murine Renal Allografts: Spontaneous Acceptance Is Associated with Regulated T Cell-Mediated Immunity

Abstract: It was shown >20 yr ago that mice will spontaneously accept renal allografts in the absence of immunosuppression, but the mechanism responsible for this is not understood. We transplanted DBA/2 (H-2d) kidneys into nephrectomized C57BL/6 (H-2b) mice, and the allografts were spontaneously accepted for >60 days without immunosuppression. In contrast, nonimmunosuppressed cardiac and skin allografts in the same strain combination are rejected within approximately 10 days. The accepted renal allografts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 32 publications
6
72
1
Order By: Relevance
“…Consistent with previous reports (19), BALB/c allografts transplanted into naive B6 hosts are spontaneously accepted and do not exhibit tubular inflammation/injury characteristic of clinical renal allograft rejection (data not shown). To circumvent this limitation, spleen cells from 2C TCR transgenic mice (H-2L d -specific TCR on Ͼ99% of peripheral CD8 cells) crossed onto either WT (2C-WT) or CD103 Ϫ/Ϫ backgrounds (2C-CD103 Ϫ/Ϫ ) were adoptively transferred into syngeneic B6 scid hosts bearing vascularized renal allografts from BALB/c (H-2L d -positive) donors.…”
Section: Cd8supporting
confidence: 79%
“…Consistent with previous reports (19), BALB/c allografts transplanted into naive B6 hosts are spontaneously accepted and do not exhibit tubular inflammation/injury characteristic of clinical renal allograft rejection (data not shown). To circumvent this limitation, spleen cells from 2C TCR transgenic mice (H-2L d -specific TCR on Ͼ99% of peripheral CD8 cells) crossed onto either WT (2C-WT) or CD103 Ϫ/Ϫ backgrounds (2C-CD103 Ϫ/Ϫ ) were adoptively transferred into syngeneic B6 scid hosts bearing vascularized renal allografts from BALB/c (H-2L d -positive) donors.…”
Section: Cd8supporting
confidence: 79%
“…Cytokine neutralization studies clearly demonstrated that TGF-␤1, not IL-10, was the principal mediator of DTH regulation in all the allograft acceptors. A TGF-␤ bias in regulated anti-donor DTH response may reflect conditions unique to tolerance induced by APCs emerging from TGF-␤-rich microenvironments, as previously suggested by studies of mouse kidney transplants (48) and the anterior chamber of the eye (49,50). Other tolerance mechanisms, including IL-10-producing allospecific T regulatory cells (8), may be required to achieve permanent, as opposed to metastable, tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Immunoregulatory mechanisms involving TGF-␤ and T regs have been identified in rodent recipients that have spontaneously accepted renal allografts, but their association with graft acceptance is poorly understood (3,6). Additionally, TGF-␤-associated immune regulation is only transiently expressed and is not observed in late renal allograft acceptor splenocytes (Ͼ150 days posttransplant) (5).…”
mentioning
confidence: 99%
“…Interestingly, spontaneous renal allograft acceptors display regulation of splenocyte alloresponse to donor Ag. Presence of alloreactive T cells and regulation are demonstrated as delayed-type hypersensitivity (DTH) 3 detectable immune regulation mediated by splenic T cells involving TGF-␤ (3,4). In addition, these allograft acceptors also develop donor-reactive Abs (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation